Development of an Automatic Compost Fertilizer Sieving Tool Using Design For Manufacture and Assembly (DFMA) Method - Wahyu Kurniawan; Akmal Suryadi (Universitas KH. Abdul Chalim Mojokerto, 2026)
Rapid technological advancements significantly impact various sectors, including agriculture, which demands high-quality products. One of the main challenges faced by Sakai Indah MSMEs is the manual compost fertilizer sieving process, which relies on conventional tools. This process is time-consuming and labor-intensive, leading to production inefficiencies, increased operational costs, and reduced competitiveness in meeting growing market demand. To address this issue, an automatic fertilizer sieving machine was developed using the Design for Manufacturing and Assembly (DFMA) method to enhance production efficiency. DFMA is a structured approach aimed at optimizing product design by reducing the number of components, improving stability, and simplifying assembly and maintenance, ultimately lowering manufacturing costs and production time. The developed iron sieving machine successfully reduced the sieving process from 800 seconds (13 minutes) to 120 seconds (2 minutes) per 50 kg of compost, enabling the MSME to efficiently handle 2,000-4,000 kg of compost per month. With 17 components, the new design improves durability, stability, and ease of assembly while reducing labor dependency. Cost analysis showed that the total manufacturing cost reached Rp7,651,000, with an assembly efficiency of 48%. These improvements significantly increase production capacity, reduce labor costs, and enhance the MSME’s ability to meet growing market demands.